1990
DOI: 10.1213/00000539-199007000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Vascular Resistance in the Isolated Canine Hindlimb After Graded Doses of Alfentanil, Fentanyl, and Sufentanil

Abstract: Under halothane anesthesia five dogs were prepared with both hindlimbs isolated from the systemic circulation to allow intermittent placement on extracorporeal perfusion at constant flow. One limb of each dog was surgically denervated. In this relatively anesthetic-free preparation, graded equivalent doses of alfentanil, fentanyl, and sufentanil were infused over 30 s, and vascular resistance was measured. Increasing opioid administration caused a progressive diminution in peripheral resistance. By the high do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
0
27
0
3
Order By: Relevance
“…Tal achado estaria relacionado à redução da resistência periférica total promovida pelo opióide, através de mecanismo de ação no sistema nervoso central (SNC), ou diretamente sobre a musculatura lisa dos vasos, como citado por White et al (1990). Já os anestésicos inalatórios halogenados, como o halotano, isofluorano ou desfluorano, tendem a reduzir a pressão arterial (PA) de modo relacionado à dose empregada.…”
Section: Resultsunclassified
“…Tal achado estaria relacionado à redução da resistência periférica total promovida pelo opióide, através de mecanismo de ação no sistema nervoso central (SNC), ou diretamente sobre a musculatura lisa dos vasos, como citado por White et al (1990). Já os anestésicos inalatórios halogenados, como o halotano, isofluorano ou desfluorano, tendem a reduzir a pressão arterial (PA) de modo relacionado à dose empregada.…”
Section: Resultsunclassified
“…However, Karasawa et al 23 reported that pretreatment with naloxone had no effect on fentanylinduced relaxation of rat aortic rings. White et al 6 found, in dogs, that pretreatment with naloxone did not alter the vascular response to fentanyl. Makita et al 24 reported that naloxone did not affect the inhibitory effect of fentanyl on the NE-induced PI response in rat cerebral cortical prisms.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there is one report that fentanyl reduced the peripheral vascular resistance t9-21 and another that fentanyl had no effect." White et al 6 found, in dogs, that high-dose fentanyl (50 ~g-kg -~) caused a decrease in peripheral vascular resistance of 48% in the isolated hindlimb, and that pretreatment with denervation did not change the response to fentanyl. They concluded that fentanyl produced vasodilatation by direct action on the peripheral vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todavia, esse parâmetro permaneceu estável ao longo de todo o período experimental, uma vez que não houve alteração das concentrações inspiradas do agente volátil. Entretanto, a adição do butorfanol causou diminuição das pressões arteriais, o que, de acordo com TYNER et al (1989), pode ser atribuído à redução da resistência periférica total (RPT) promovida pelo agente devido à ação do fármaco no sistema nervoso central, ou diretamente sobre a musculatura lisa dos vasos (WHITE et al, 1990). Ainda quanto às pressões arteriais, pode ter ocorrido efeito aditivo do desfluorano aos do opióide sobre a musculatura vascular, facilitando o relaxamento e propiciando esta diminuição de pressão (RODIG et al, 1997).…”
Section: Discussionunclassified